2016
DOI: 10.1111/acfi.12247
|View full text |Cite
|
Sign up to set email alerts
|

The impact of undergraduate personal finance education on individual financial literacy, attitudes and intentions

Abstract: Financial literacy education features prominently among the policy options available to improve personal financial decision-making. Notwithstanding calls to expand delivery of financial literacy units at university level, such offerings are relatively rare with little evaluation. We provide an evaluation of the impact on financial literacy, financial attitudes and financial behaviour intentions of a semester unit in personal finance delivered to undergraduates at an Australian university, carefully controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 38 publications
3
45
0
1
Order By: Relevance
“…A number of studies recommend financial education programs to improve people's financial literacy (Gerrans and Heaney, 2016). However, those who are much older and face declining health are less likely to engage in those education programs.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies recommend financial education programs to improve people's financial literacy (Gerrans and Heaney, 2016). However, those who are much older and face declining health are less likely to engage in those education programs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies which have explored the impact of personality or behavioural traits on financial literacy find that extroversion is negatively linked to financial literacy (Gerrans & Heaney, 2016;Killins, 2017). In the Killins (2017) study conscientiousness had a positive effect on financial literacy, whereas in Gerrans and Heaney (2016) it was only significant for advanced financial literacy concepts.…”
Section: Previous Researchmentioning
confidence: 99%
“…Studies which have explored the impact of personality or behavioural traits on financial literacy find that extroversion is negatively linked to financial literacy (Gerrans & Heaney, 2016;Killins, 2017). In the Killins (2017) study conscientiousness had a positive effect on financial literacy, whereas in Gerrans and Heaney (2016) it was only significant for advanced financial literacy concepts. From a gender perspective it may be that the observed gender gaps in financial literacy derives from gender differences in psychological characteristics, including characteristics such as confidence (Bucher-Koenen et al, 2017).…”
Section: Previous Researchmentioning
confidence: 99%
“…In the United States, policymakers improve and strengthen consumer financial capabilities through education on basic financial knowledge. A survey from the undergraduates at an Australian university showed that financial education led to a positive increase in objective and subjective financial literacy, which improved personal financial decision-making [16]. In general, financial education can be divided into professional financial education and public financial education [17].…”
Section: Introductionmentioning
confidence: 99%